OPTIMALISASI JUMLAH PRODUKSI MENGGUNAKAN PEMROGRAMAN LINIER UNTUK MAKSIMALISASI KEUNTUNGAN PADA KONVEKSI YMF.ID KABUPATEN BANDUNG - Anggi; Bambang Handoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to optimize gamis production at Konveksi YMF.id in Bandung Regency to maximize profit. This MSME faces challenges in production effectiveness due to limited resources and fluctuating market demand. The method employed is the simplex linear programming approach, aided by POM-QM software, utilizing a quantitative, exploratory, and descriptive research design. Primary data was collected through in-depth interviews and direct observation, while secondary data was obtained from production records and relevant financial reports. The analysis results indicate that by producing 173 Yumma gamis, 876 Kayla gamis, and 1600 Inara gamis, Konveksi YMF.ID can achieve an optimal profit of Rp 22,266,102. This represents a profit increase of Rp 880,439 or 4.12% from the previous actual profit of Rp 21,385,663. The implementation of this method helps the company avoid common problems like overproduction or underproduction and significantly increases profitability.